An integrative approach to leader development connecting adult development, identity, and expertise / David V. Day, Michelle M. Harrison, Stanley M. Halpin - Day, David V. 1956-; Harrison, Michelle M.; Halpin, Stanley M. (Routledge, 2009)
This book is a beginning, a first step, in taking leader development in organizations beyond conventional wisdom toward a scientifically sound research-based set of principles and practices. The authors looked beyond their own academic disciplines to bring to bear accumulated wisdom from researchers who have developed well-established and accepted theoretical perspectives on adult development processes in general, then wove in the ideas that have emerged in more targeted research on adult education, development of cognitive skills, identity development, self-regulation, moral and ethical development, and related topics. The authors present an integrative theory that provides a coherent framework for describing and understanding how leader development takes place.